Multiple plasmodium falciparum merozoite surface protein 1 complexes mediate merozoite binding to human erythrocytes - Lin, Clara S.; Uboldi, Alessandro D.; Epp, Christian; Bujard, Hermann; Tsuboi, Takafumi; Czabotar, Peter E.; Cowman, Alan F. (The journal of biological chemistry, 2016)
Successful invasion of human erythrocytes byPlasmodium falciparummerozoites is required for infection of the host and parasite survival. The early stages of invasion are mediated via merozoite surface proteins that interact with human erythrocytes. The nature of these interactions are currently not well understood, but it is known that merozoite surface protein 1 (MSP1) is critical for successful erythrocyte invasion. Here we show that the peripheral merozoite surface proteins MSP3, MSP6, MSPDBL1, MSPDBL2, and MSP7 bind directly to MSP1, but independently of each other, to form multiple forms of the MSP1 complex on the parasite surface. These complexes have overlapping functions that interact directly with human erythrocytes. We also show that targeting the p83 fragment of MSP1 using inhibitory antibodies inhibits all forms of MSP1 complexes and disrupts parasite growthin vitro.